2017 IEEE International Symposium on Mixed and Augmented Reality (ISMAR-Adjunct) 2017
DOI: 10.1109/ismar-adjunct.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Towards Engaging Upper Extremity Motor Dysfunction Assessment Using Augmented Reality Games

Abstract: Advances in technology offer new opportunities for a better understanding of how different disorders affect motor function. Our aim is to explore the potential of augmented reality (AR) using free hand and body tracking to develop engaging games for a uniform, cost-effective and objective evaluation of upper extremity motor dysfunction in different patient groups. Based on the insights from a study with 20 patients (10 Parkinson's Disease patients and 10 stroke patients) who performed hand/arm movement tasks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…From the reviews, most studies had been conducted in Europe which is 15 studies [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19] followed by USA which is nine studies [2], [20][21][22][23][24][25][26][27], Korea [28,29], and South East Asia [30][31][32][33] had been handled 3 studies respectively, while China has 2 studies [34,35] and Turkey [36] and Brazil [37] and Japan [38] had one paper respectively. The papers had been published in the early 2000s until the present.…”
Section: Fig 1 Selection Of Study Processmentioning
confidence: 99%
See 2 more Smart Citations
“…From the reviews, most studies had been conducted in Europe which is 15 studies [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19] followed by USA which is nine studies [2], [20][21][22][23][24][25][26][27], Korea [28,29], and South East Asia [30][31][32][33] had been handled 3 studies respectively, while China has 2 studies [34,35] and Turkey [36] and Brazil [37] and Japan [38] had one paper respectively. The papers had been published in the early 2000s until the present.…”
Section: Fig 1 Selection Of Study Processmentioning
confidence: 99%
“…The previous study and investigation have shown that healthy and technology have close associated which means it important to help the user to improve or assist their daily routine. Another study that evaluates the augmented reality games as a supportive technology application that has been used for hand motor-impaired user [3], [15], [19], [28]. Besides that, there is a study that used another device which is exoskeleton technology for hand motor impaired users' [10], [4], [25], [27].…”
Section: Fig 1 Selection Of Study Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessibility of consumer AR systems is growing and the adoption of AR systems into application domains is becoming commonplace [14]. With the recent advances in consumer hardware and the integration of on-board sensor technology, interactive AR applications in healthcare [15,18], education [13] and industry [19] are now possible. This advanced hardware is driving the integration of AR into the workplace with many industries keen on applying AR into their work-flow processes [22].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers are currently evolving gesture interactions into physical interactions, thus, completely mimicking the interaction performed in the real world, into AR environments [46,49]. The work of Al-Kalbani et al [4] and [5] have sought to understand the complex nature of the human grasp for freehand interaction and defined the problems associated with grasping objects in AR, Ciodota et al [15] evaluated the application of grasps in AR and also Swan et al [51] evaluated the problems associated with representing and reaching the true located space of augmented objects.…”
Section: Interaction Approachesmentioning
confidence: 99%